Recent Developments in HLA B27 Anterior Uveitis - Wakefield, Denis; Clarke, Daniel; McCluskey, Peter (Frontiers in Immunology, 2021)
There has been steady progress in understanding the pathogenesis, clinical features, and effective treatment of acute anterior uveitis (AU) over the past 5 years. Large gene wide association studies have confirmed that AU is a polygenic disease, with overlaps with the seronegative arthropathies and inflammatory bowel diseases, associations that have been repeatedly confirmed in clinical studies. The role of the microbiome in AU has received increased research attention, with recent evidence indicating that human leukocyte antigen B27 (HLA B27) may influence the composition of the gut microbiome in experimental animals. Extensive clinical investigations have confirmed the typical features of acute AU (AAU) and its response to topical, regional and systemic immunosuppressive treatment. Increased understanding of the role of cytokines has resulted in studies confirming the value of anti-cytokine therapy [anti–tumor necrosis factor (anti-TNF) and interleukin 6 (IL-6) therapy] in severe and recurrent cases of AAU, particularly in subjects with an associated spondyloarthopathy (SpA) and in juvenile idiopathic arthritis (JIA)–associated AAU.